O jogo digital se-pa-re como ferramenta educacional para o processo de ensino-aprendizagem da educação ambiental - LOBO, Helen Tatiana Ataide (2020)
It is recognized that in today's world, our society is surrounded by technologies, whether by means of computers or cell phones... and why education is still stagnant in a traditional mold where there is classroom, portfolios lined up, white board (or blackboard), being that we are in a digital age and that education can use technology and Gamification in its favor to enhance the process of teaching and learning. This research aimed to describe the experience and the use of the SE-PA-RE educational software, with environmental themes, as a tool that can aid the teaching and learning process with students of the 6th grade of Elementary School II of the Salesian School of Work (EST). The activity was performed in the computer room of the EST, and the data obtained from this research were quantitatively and qualitatively analyzed, based on observation and records made by the researcher. The SE-PA-RE software was received and evaluated by students and teachers, consuming the trend of modernization of education and teaching and learning.